Domain B of ARS307 contains two functional elements and contributes to chromosomal replication origin function. - Theis, J F (1994)
ARS307 is highly active as a replication origin in its native location on chromosome III of Saccharomyces cerevisiae. Its ability to confer autonomous replication activity on plasmids requires the presence of an 11-bp autonomously replicating sequence (ARS) consensus sequence (ACS), which is also required for chromosomal origin function, as well as approximately 100 bp of sequence flanking the ACS called domain B. To further define the sequences required for ARS function, a linker substitution mutagenesis of domain B was carried out. The mutations defined two sequences, B1 and B2, that contribute to ARS activity. Therefore, like ARS1, domain B of ARS307 is composed of functional subdomains. Constructs carrying mutations in the B1 element were used to replace the chromosomal copy of ARS307. These mutations caused a reduction in chromosomal origin activity, demonstrating that the B1 element is required for efficient chromosomal origin function.